Muddy Waters: Unintentional Consequences of Blue Carbon Research Obscure Our Understanding of Organic Carbon Dynamics in Seagrass Ecosystems - Belshe, E. Fay; Mateo, Miguel A.; Gillis, Lucy; Zimmer, Martin; Teichberg, Mirta (Frontiers in Marine Science, 2017)
The recent surge in research on organic carbon sequestration by seagrass ecosystems has begun to reveal the complexity of the carbon cycle within these ecosystems. In this prospective we discuss two areas of investigation that require further scrutiny: 1) why organic carbon is stabilized in seagrass sediments, and 2) how long organic carbon resides within these sediments. By delving into these topics, pointing out current pitfalls, and highlighting methodological advances, our motive is to focus future efforts and provide a frame work to manage the complexity found within the diverse seagrass bioregions. The high rate of seagrass degradation and loss, coupled with increasing atmospheric CO2 concentrations gives precedence to these lines of research, which require rigorous reevaluation if we are to substantially advance our understanding of OC dynamics in seagrass ecosystems.